Análise do exercício profissional do (a) assistente social na política de proteção social básica nos Centros de Referência da Assistência Social: saberes em questão - Vieira, Marciana Artico (2011)
The National Social Policy in 2004 points to the construction of the Unified Social Assistance, which aims to reorganize the system of social protection in the Social Policy in Brazil. To ground the discussion, literature search was conducted and also in the field, with five social workers, in order to analyze the approaches and departures of professional practice based on the ethicalpolitical project of the Social Work and the new management of the Social Assistance Policy. The research presents important advances of the Social Policy and its interface with the Social Work, as well as the principles and guidelines of the National Social Policy, of His (in conjunction with the NOB/SUAS/2005 and NOB / RH / SUAS/2005) and the new form of organization of basic social protection implemented by the Reference Center for Social Assistance (CRAS), with a penchant for professional Social Worker, identifying the strengths and weaknesses of professional intervention in this space work. The research consists of two empirical CRAS in the municipality of Votuporanga (SP), whose main objective to develop services, programs and projects within the basic social protection. The research demonstrates the need for reflection on the theoretical and methodological aspects, ethical-political and technical-operative of Social Work, revealing that the qualification process and training should be ongoing